Theory Versus Practice in Risk Analysis: An Empirical Study: A Comment. - Hoskins, C. G. (The Accounting Review, 1975)
Abstract This article presents comments of the author on the paper "Theory Versus Practice in Risk Analysis: An Empirical Study," by W.R. Greer that was published in the July 1974 of the periodical "The Accounting Review." In his paper, Greer concluded that there appears to be a substantial conflict between the decision processes used by actual decision makers and existing utility theory. The conflict seems to center around the inability of classical utility theory to deal effectively with situations where one or more of the contingent outcomes for a project are lower than some critical amount. The form of utility function employed by Greer was the utility of an investment opportunity is an increasing function of the expected value of that opportunity and a decreasing function of the risk of the opportunity. Greer employed the standard deviation of payoffs as the measure of risk. This comment contends that the actual decisions of the firms in Greer's study are not inconsistent with a utility function of the form described if instead semi-variance is used as the measure of risk.